Research challenges for eco-efficient and circular industrial systems - Despeisse, Mélanie; Acerbi, Federica; Arioli, Veronica; Childe, Stephen; Colombo, Beatrice; Evans, Steve; González Chávez, Clarissa A.; Jones, Saul; Nujen, Bella B.; Pezzotta, Giuditta; Powell, Daryl; Toller Melén, Carl; et al. (Springer, 2024)
The field of industrial sustainability is rapidly expanding with new concepts and frameworks emerging almost daily. At the same time, mature ones are being used in new applications and combined with new technologies and methodologies. While these developments are promising, the ambitions, scale, and speed of the change required to meet sustainability goals urgently need to increase. To accelerate industrial sustainability research and its impact, experts were invited to discuss research challenges in a webinar series focused on ten priority areas for eco-efficient and circular industrial systems. This paper presents the research challenges discussed to share sustainability practices, stimulate collaborations, and inspire change for more impactful applied research and knowledge transfer to industry.
Keywords: 46 Information and Computing Sciences; 12 Responsible Consumption and Production; 46 Information and computing sciences